Mildew-proof beautifying alcohol-permeable glue and preparation process thereof
By complexing diatomaceous earth with zinc ions to form a metal organic frame structure, the anti-molded beauty alcohol permeable formula is solved, and the problem of mildew permeability of beauty alcohol permeable is achieved, long-term antibacterial and mildew resistance and thermal stability is achieved, and the transparency and mechanical properties of the colloid are improved.
Patent Information
- Application Number
- CN202510949444.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-08-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cosmetic alcohol permeable gel is susceptible to microorganisms to cause mold and discoloration, affecting performance and aesthetics. The anti-mold agents on the market have problems such as poor heat resistance, easy decomposition, toxicity and environmental pollution.
The anti-mold-resistant cosmetic alcohol permeable formula containing fillers such as titanium dioxide, nano zinc oxide, diatomaceous earth, etc. is adopted to form a metal organic frame structure by complexing modified diatomaceous earth with zinc ions, and combine specific crosslinking agents and plasticizers to improve the antibacterial and anti-mold properties and thermal stability of the colloid.
It achieves long-term antibacterial and mildew resistance in humid environments, maintains the transparency and physical properties of the colloid, reduces environmental pollution, and improves the thermal stability and mechanical properties of the colloid.
Smart Images

Figure IMAGE_EE1D1352-F4F8-4239-92DF-9D61028B8BAC
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dealcoholized silicone adhesives, in particular to a mildew-proof beauty alcohol-penetrating adhesive and a preparation process thereof. Background Art
[0002] Beauty glue, also known as edge sealing glue or finishing glue, is a new type of adhesive for home furnishing finishing materials, primarily used to beautify and protect gaps in homes, achieving bonding and sealing. The vast majority of beauty glues on the market are silicone-based, using polydimethylsiloxane as the primary raw material, supplemented by crosslinkers, coupling agents, and colorants. They cure at room temperature by reacting with moisture in the air. Based on the products released during the curing process, beauty glues are primarily categorized as deoximation, deacetation, dealcoholation, deacetonation, and deaminement. These deoximation, deacetation, deacetonation, and deaminement types release small molecules such as butanone oxime, acetic acid, acetone, and amines / ammonia during curing. These can be toxic or irritating, potentially harmful to human health and the environment, or highly corrosive, making them unsuitable for sensitive surfaces. When the dealcoholized (alcohol type) beauty glue solidifies, the small molecules released are generally methanol, ethanol and other alcohol molecules, which are non-toxic, non-irritating, healthier and more environmentally friendly; they have low corrosiveness and high transparency and stability.
[0003] Alcohol-based transparent adhesive, also known as alcohol-transparent adhesive, is commonly used in high-humidity areas. It is susceptible to microbial attack, leading to mold and discoloration, which affects the performance and aesthetics of the adhesive. Therefore, a certain amount of mildew inhibitors must be added to the formulation to improve its mildew resistance. Mildew inhibitors on the market primarily come from inorganic, organic, and natural biological sources. Organic types, such as quaternary ammonium salts, biguanides, alcohols, phenols, pyridines, imidazoles, isothiazolinones, and organometallics, offer broad-spectrum, rapid bactericidal properties and are easily soluble in colloids. However, they generally have poor heat resistance, are prone to decomposition, and have a short antibacterial and mildew-proofing effect. Some mildew inhibitors also have negative effects such as toxicity and environmental pollution. Inorganic mildew inhibitors, such as metallic inorganic salts, nano-titanium dioxide, nano-tin dioxide, and nano-silver, offer broad-spectrum, long-lasting antibacterial properties, excellent heat resistance, and resistance to drug resistance. However, they also have limited mildew resistance, poor effectiveness in humid environments, yellowing, and high hardness. Therefore, we propose a mildew-proof beauty alcohol permeable glue and a preparation process thereof. Summary of the Invention
[0004] The object of the present invention is to provide a mildew-proof cosmetic alcohol permeable glue and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a mildew-proof beauty alcohol permeable glue, comprising the following components: 80 to 100 parts of alkoxy-terminated polydimethylsiloxane, 7 to 20 parts of plasticizer, 6 to 18 parts of filler, 5 to 15 parts of cross-linking agent, 1.2 to 2.0 parts of mildew inhibitor, and 0.2 to 2.5 parts of catalyst.
[0006] Furthermore, the filler is a mixture of one or more of titanium dioxide, nano zinc oxide, diatomaceous earth, and fumed silica.
[0007] Furthermore, the crosslinking agent is a mixture of one or more of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, [3-(morpholinyl)propyl]trimethoxysilane, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and diisopropyl bis(ethyl acetoacetate)titanate.
[0008] Furthermore, the plasticizer is a mixture of one or more of methyl silicone oil, dimethyl silicone oil, white oil, diisononyl phthalate, and quaternary ammonium modified silicone oil.
[0009] Furthermore, the catalyst is one of dibutyltin dilaurate and dibutyltin bis(acetylacetonate).
[0010] A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Alkoxy-terminated polydimethylsiloxane, a crosslinking agent, a mildew preventer, a catalyst, and fumed silica were mixed and stirred and dispersed in a double planetary mixer at a stirring rate of 90 to 120 rpm and a dispersion rate of 7000 to 9500 rpm for 1 to 2 hours; fillers and plasticizers were added and stirred and dispersed for 1 to 2 hours at a stirring rate of 160 to 190 rpm and a dispersion rate of 10000 to 13000 rpm to obtain an alcohol-permeable adhesive.
[0011] Furthermore, the crosslinking agent includes the following components: by mass, 25 to 40 parts of vinyltrimethoxysilane, 11 to 13 parts of diisopropyl bis(ethyl acetoacetate) titanate, 47 to 62 parts of 3-aminopropyltrimethoxysilane, 5 to 10 parts of [3-(morpholinyl)propyl]trimethoxysilane and 5 to 10 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0012] Furthermore, the plasticizer includes the following components: 10 to 90% by mass of dimethyl silicone oil and 10 to 90% by mass of quaternary ammonium modified silicone oil.
[0013] Furthermore, the filler is a mixture of diatomaceous earth and fumed silica, with a mass ratio of 10:(0.3-1.5).
[0014] In the above technical solution, alkoxy-terminated polydimethylsiloxane is the main component, siloxane is the cross-linking agent, and plasticizers and fillers are added to prepare alcohol-permeable glue. The cross-linking agent can be selected to add morpholinosiloxane or ammonium chloride siloxane, and the plasticizer can be partially added with quaternized modified silicone oil, which is synergistic with the mildew inhibitor, so that the alcohol-permeable glue can play an antibacterial and mildew-proof effect, and has a relatively good broad-spectrum, rapid bactericidal property and thermal stability. It also has a long-lasting mildew-proof effect in a humid environment, and has no obvious effect on the appearance of the alcohol-permeable glue. The addition of the above-mentioned cross-linking agent and plasticizer components enhances the hydrophilicity of the alcohol-permeable glue to a certain extent, shortens the surface drying time of the colloid, and increases the cross-linking density of the system. As a home furnishing edge adhesive material, the mechanical properties and thermal stability of the alcohol-permeable glue are improved after curing.
[0015] Furthermore, the diatomaceous earth is modified, and the specific modification process is as follows: Add silicate to the diatomaceous earth suspension, raise the temperature to 60-65°C within 2 hours, adjust the pH of the system to 6.5-7.0, and stir the reaction for 30-40 minutes; The organic ligand and zinc nitrate are mixed in N,N-dimethylformamide, added to the above diatomaceous earth suspension, stirred and heated to 60-75°C, and reacted for 24-72 hours; the pH of the system is adjusted to 6.9-7.3, and the reaction is continued for 20-40 minutes; centrifuged, dried, and crushed to obtain modified diatomaceous earth.
[0016] Furthermore, the mass concentration of the diatomaceous earth suspension is 8 to 20%; The silicate is one of sodium silicate, potassium silicate and water glass, and the dosage is 5-15% of the mass of diatomaceous earth; The dosage of zinc nitrate is 2-10% of the mass of diatomaceous earth; The amount of organic ligand used is 0.4-2.0% of the mass of diatomite; The ratio of organic ligand and N,N-dimethylformamide is (1.0-1.6) g / 100 mL; Furthermore, the drying process is as follows: drying at a temperature of 90 to 110° C. to a constant weight; After crushing, the particle size of diatomaceous earth is 0.03 to 3 μm.
[0017] In the above technical solution, the diatomaceous earth is selected from micro-nano calcined diatomaceous earth, which has a good match with the selected fumed silica in terms of particle size, which helps to disperse the filler and reduce refraction. The filler has good transparency, and its refractive index is close to that of the resin system in the colloid, so that it has little effect on the transparency and haze of the colloid. After mixing with the resin, it can give the resin / prepared colloid good transparency and physical properties.
[0018] Before use, diatomaceous earth is modified. The specific process is as follows: silicate is added to a diatomaceous earth suspension, hydrolyzed to form a silica sol, and then coated on the diatomaceous earth surface. During the silica sol formation process, an organic ligand and zinc nitrate are mixed and added to the diatomaceous earth suspension. Under the action of heat, the organic ligand and zinc ion complex to form a metal-organic framework structure. After the reaction is completed, the system pH is adjusted again to convert the unreacted zinc ions into zinc hydroxide, which is then loaded onto the diatomaceous earth surface along with the silica sol and metal-organic framework. After drying, a silicon oxide coating doped with the metal-organic framework and zinc oxide is formed, achieving surface modification of the diatomaceous earth.
[0019] Zinc ions, as non-toxic antimicrobial cations, possess bactericidal and anti-inflammatory properties. They can alter the permeability of cell membranes, causing leakage of their contents and leading to cell death. They can also damage DNA or proteases, promoting cross-linking and structural breakdown of DNA molecules, leading to cell death or loss of the ability to divide and proliferate. They can react with sulfhydryl and amino groups in cellular proteins, reducing the activity of dehydrogenases and disrupting the cell's electron transport, respiratory, and material transport systems. They can also induce cells to produce large amounts of ROS, accelerating cell death. Zinc ions also have excellent water stability. Complexing zinc ions with organic ligands to form a metal-organic framework (MOF), coated on the surface of diatomaceous earth, offers superior water and thermal stability. The framework slowly degrades, allowing for the sustained release of zinc ions, ensuring the stability and long-lasting antibacterial and antifungal properties of the modified diatomaceous earth and the resulting colloids.
[0020] The addition of silica to the diatomite surface reduces its surface water absorption and chemical reactivity, helping to improve the durability of the resulting colloid and promoting its continued antibacterial and mildew-proofing properties. It also enhances the surface hardness, strength, and wear resistance of the modified diatomite. By partially or completely replacing the diatomite in the colloid, silica can enhance the mechanical properties of the resulting colloid. Furthermore, silica can reduce the modified diatomite's oil absorption and absorption of organic components, helping to fully utilize the properties of each component and enhancing system stability.
[0021] Furthermore, the organic ligand is prepared by the following process: 2,5-dihydroxyterephthalic acid, dibromo compound, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide, heated to 100-105°C, stirred and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand.
[0022] Furthermore, the mass ratio of 2,5-dihydroxyterephthalic acid, dibromo compound, and potassium carbonate is 10:(28.8-29.1):(28.2-30.7); The ratio of 2,5-dihydroxyterephthalic acid and mixed solution is (3-4) g / 100 mL; The volume ratio of acetone and dimethyl sulfoxide is 1: (2.0~2.5).
[0023] Further, the dibromo compound is prepared by the following process: Add magnesium metal and iodine to anhydrous tetrahydrofuran, and slowly add thiazolylbenzimidazole-6-bromide under nitrogen atmosphere. After the addition is complete, heat to 60-65°C and react for 150-200 minutes to obtain thiazolylbenzimidazole magnesium bromide. Add metallic magnesium and iodine to anhydrous tetrahydrofuran, and slowly add 4,5-dibromoimidazole under nitrogen atmosphere. After the addition is complete, raise the temperature to 60-65°C and react for 150-200 minutes to obtain imidazolyl magnesium bromide. Mix cyanuric chloride and anhydrous tetrahydrofuran, slowly add thiazolylbenzimidazole magnesium bromide, add completely over 30 minutes, and stir to react for 2 to 3 hours; add imidazolylmagnesium bromide, heat to 60 to 65°C, and stir to react for 2 to 3 hours; raise the temperature to 85 to 90°C, and continue to react for 2.5 to 3.5 hours; add aqueous ammonium chloride solution, extract with dichloromethane, dry over anhydrous sodium sulfate, filter, rotary evaporate the filtrate, and column column to obtain a dibromo compound.
[0024] Furthermore, the mass ratio of thiazolylbenzimidazole-6-bromide (CAS No: 916-50-5), metallic magnesium, and iodine is 10: (0.95-1.05): (0.2-0.4); The ratio of thiazolylbenzimidazole-6-bromide and anhydrous tetrahydrofuran is (25-28) g / 100 mL.
[0025] Furthermore, the mass ratio of 4,5-dibromoimidazole, metallic magnesium, and iodine is 10:(2.37-2.50):(0.5-0.8); The ratio of 4,5-dibromoimidazole to anhydrous tetrahydrofuran is (25-28) g / 100 mL.
[0026] Furthermore, the mass ratio of cyanuric chloride, thiazolylbenzimidazole magnesium bromide, and imidazolylmagnesium bromide is 10: (16.5-17.3): (32.7-35.7); The ratio of cyanuric chloride to anhydrous tetrahydrofuran is (10-15) g / 100 mL.
[0027] In the above technical solution, the organic ligand is obtained by polymerizing 2,5-dihydroxyterephthalic acid and a dibromo compound. Its carboxyl group can serve as an effective ligand structure for zinc ions, thereby forming a metal-organic framework with the zinc ion. The preparation process of the dibromo compound is as follows: thiazolylbenzimidazole-6-bromide and 4,5-dibromoimidazole are used as raw materials to prepare thiazolylbenzimidazole magnesium bromide and imidazolylmagnesium bromide. These are then reacted with cyanuric chloride. By controlling the amount of the two substances, a compound with a dibromo (or polybromo) structure is formed. This structure contains imidazolyl, thiazolyl, and benzimidazole groups, which can form coordination with zinc ions and exhibit good antimicrobial activity. This increases the content of antimicrobial components in the colloid and helps maintain the colloid's long-term antifungal properties. The metal-organic framework formed by the organic ligand and zinc ion has a large porosity, which facilitates the interpenetration of silica sol, zinc hydroxide, and crosslinking agent within its pores, further improving the stability of the modified diatomaceous earth, the colloid, and its antifungal and antimicrobial properties in aqueous and thermal environments.
[0028] Furthermore, the fumed silica is surface treated, and the specific process is as follows: The fumed silica and ethanol are mixed and ultrasonically treated for 60 minutes; a surfactant is added and ultrasonically dispersed for 30 minutes; the mixture is heated to 65-85° C. and stirred at a speed of 550-650 rpm for 1-2 hours; the mixture is centrifuged, dried, ground and sieved to obtain the product.
[0029] Furthermore, the amount of surfactant used is 3 to 15% of the mass of the fumed silica; Ethanol is anhydrous ethanol or 95v% ethanol solution; The ratio of fumed silica to ethanol is (5-10) g / 100 mL.
[0030] Furthermore, the surfactant is one of stearic acid, sodium lauryl sulfate, silane coupling agent KH550, silane coupling agent KH570, and titanate coupling agent N-201.
[0031] Furthermore, when the surfactant is selected from silane coupling agent KH570 or titanate coupling agent N-201, the pH of the system is adjusted to be weakly alkaline.
[0032] In the above technical solution, when the surface-modified filler is applied to alkoxy-terminated polydimethylsiloxane, it has good dispersion, promotes the uniform distribution of the filler, effectively improves the mechanical properties and thermal properties of the colloid, and reduces the micro-refraction phenomenon of the colloid, thereby improving the transparency of the prepared colloid. DETAILED DESCRIPTION
[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0034] In the following specific embodiments, the percentages are all percentages by mass, and the "parts" are all parts by mass; Diatomaceous earth: particle size ≤ 2.48 μm, D50 = 1.53 μm, sourced from Jilin Changbaishan Chemical Co., Ltd.; before use, heat at 180°C for 90 min, then raise the temperature to 600°C and hold for 4 h; Fumed silica: H-18, from Wacker, Germany; Alkoxy-terminated polydimethylsiloxane: J-200, viscosity 20,000 mPa·s, from Jiangsu Kexing New Materials Co., Ltd. Dimethyl silicone oil: 201, viscosity 100 mPa·s, from Bluestar Chemical New Materials Co., Ltd. Quaternary ammonium modified silicone oil: TEGOPREN 6923, from Evonik, Germany; Antifungal agent: a mixture of JKCIDE-ST3200, JKCIDE-SZ99P, and JKCIDE-SBE560, with a mass ratio of 1:1:1, from Yancheng Juke Chemical Co., Ltd. The catalyst is dibutyltin dilaurate; The fumed silica was surface treated by mixing fumed silica and anhydrous ethanol and ultrasonically treating them for 60 minutes; adding 6% of a surfactant, sodium lauryl sulfate, and ultrasonically dispersing them for 30 minutes; heating to 85°C and stirring at 600 rpm for 1.5 hours; centrifuging, drying, grinding, and sieving to obtain the obtained product; the ratio of fumed silica to ethanol was 5 g / 100 mL; The particle size of the modified diatomaceous earth after crushing is 0.03 to 3 μm.
[0035] Example 1: A process for preparing a mildew-proof beauty alcohol permeable glue, comprising the following steps: Step 1.1. Add metallic magnesium and iodine to anhydrous tetrahydrofuran, and slowly add thiazolylbenzimidazole-6-bromide under a nitrogen atmosphere. After the addition is complete, the temperature is raised to 60° C. and the reaction is carried out for 200 minutes to obtain thiazolylbenzimidazole magnesium bromide; the mass ratio of thiazolylbenzimidazole-6-bromide, metallic magnesium, and iodine is 10:0.95:0.2; and the ratio of thiazolylbenzimidazole-6-bromide to anhydrous tetrahydrofuran is 25 g / 100 mL; Magnesium metal and iodine were added to anhydrous tetrahydrofuran, and 4,5-dibromoimidazole was slowly added under nitrogen atmosphere. After the addition, the temperature was raised to 60°C and the reaction was carried out for 200 minutes to obtain imidazolyl magnesium bromide. The mass ratio of 4,5-dibromoimidazole, magnesium metal, and iodine was 10:2.37:0.5; the ratio of 4,5-dibromoimidazole to anhydrous tetrahydrofuran was 25g / 100mL. Mix cyanuric chloride and anhydrous tetrahydrofuran, slowly add thiazolylbenzimidazole magnesium bromide over 30 minutes, and stir to react for 2 hours; add imidazolylmagnesium bromide, heat to 60°C, stir to react for 2 hours; raise the temperature to 85°C, and continue to react for 3.5 hours; add aqueous ammonium chloride solution, extract with dichloromethane, dry with anhydrous sodium sulfate, filter, and rotary evaporate the filtrate and pass through a column to obtain a dibromo compound; the mass ratio of cyanuric chloride, thiazolylbenzimidazole magnesium bromide, and imidazolylmagnesium bromide is 10:16.5:32.7; the ratio of cyanuric chloride to anhydrous tetrahydrofuran is 10g / 100mL; Step 1.2, 2,5-dihydroxyterephthalic acid, a dibromo compound, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide in a volume ratio of 1:2.0, heated to 100°C, stirred, and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand; the mass ratio of 2,5-dihydroxyterephthalic acid, dibromo compound, and potassium carbonate is 10:28.8:28.2; the ratio of 2,5-dihydroxyterephthalic acid to the mixture is 3 g / 100 mL; Step 1.3, to a 15% diatomaceous earth suspension, 5% sodium silicate was added, the temperature was raised to 60°C within 2 hours, the pH of the system was adjusted to 6.5, and the reaction was stirred for 30 minutes; 0.4% organic ligand and 2% zinc nitrate were mixed in N,N-dimethylformamide, added to the above diatomaceous earth suspension, stirred and heated to 60°C, and reacted for 24 hours; the pH of the system was adjusted to 6.9, and the reaction was continued for 20 minutes; centrifuged, dried to constant weight at 90°C, and crushed to obtain modified diatomaceous earth; the ratio of organic ligand to N,N-dimethylformamide was 1.0 g / 100 mL; Step 2: Mix the alkoxy-terminated polydimethylsiloxane, the crosslinking agent, the mildew inhibitor, the catalyst, and the fumed silica, stir and disperse them in a double planetary mixer at a stirring rate of 90 rpm and a dispersion rate of 7000 rpm for 1 hour; add the filler and the plasticizer, stir and disperse them at a stirring rate of 160 rpm and a dispersion rate of 10000 rpm for 2 hours to obtain an alcohol-permeable glue; comprising the following components: 90 parts of alkoxy-terminated polydimethylsiloxane, 10 parts of plasticizer, 6 parts of filler, 0.6 parts of fumed silica, 5 parts of crosslinking agent, 1.2 parts of mildew inhibitor, and 0.2 parts of catalyst; The crosslinking agent includes 40 parts of vinyltrimethoxysilane, 13 parts of diisopropyl bis(ethyl acetoacetate) titanate, 62 parts of 3-aminopropyltrimethoxysilane, 10 parts of [3-(morpholinyl)propyl]trimethoxysilane and 5 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; the filler is a mixture of diatomaceous earth and fumed silica with a mass ratio of 10:0.3; the diatomaceous earth contains 10% modified diatomaceous earth.
[0036] Example 2: A process for preparing a mildew-proof beauty alcohol permeable glue, comprising the following steps: Step 1.1. Add metallic magnesium and iodine to anhydrous tetrahydrofuran, and slowly add thiazolylbenzimidazole-6-bromide under a nitrogen atmosphere. After the addition is complete, raise the temperature to 62° C. and react for 180 minutes to obtain thiazolylbenzimidazole magnesium bromide; the mass ratio of thiazolylbenzimidazole-6-bromide, metallic magnesium, and iodine is 10:1.0:0.3; and the ratio of thiazolylbenzimidazole-6-bromide to anhydrous tetrahydrofuran is 27 g / 100 mL; Magnesium metal and iodine were added to anhydrous tetrahydrofuran, and 4,5-dibromoimidazole was slowly added under nitrogen atmosphere. After the addition was complete, the temperature was raised to 62°C and the reaction was carried out for 180 minutes to obtain imidazolyl magnesium bromide. The mass ratio of 4,5-dibromoimidazole, magnesium metal, and iodine was 10:2.45:0.7; the ratio of 4,5-dibromoimidazole to anhydrous tetrahydrofuran was 26g / 100mL. Mix cyanuric chloride and anhydrous tetrahydrofuran, slowly add thiazolylbenzimidazole magnesium bromide over 30 minutes, and stir to react for 2.5 hours; add imidazolylmagnesium bromide, heat to 62°C, stir to react for 2.5 hours; raise the temperature to 88°C, and continue to react for 3 hours; add ammonium chloride aqueous solution, extract with dichloromethane, dry with anhydrous sodium sulfate, filter, and rotary evaporate the filtrate and pass through a column to obtain a dibromo compound; the mass ratio of cyanuric chloride, thiazolylbenzimidazole magnesium bromide, and imidazolylmagnesium bromide is 10:17.0:34.2; the ratio of cyanuric chloride to anhydrous tetrahydrofuran is 12g / 100mL; Step 1.2: 2,5-dihydroxyterephthalic acid, a dibromo compound, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide in a volume ratio of 1:2.2, heated to 102° C., stirred, and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand; the mass ratio of 2,5-dihydroxyterephthalic acid, dibromo compound, and potassium carbonate is 10:29.0:29.5; the ratio of 2,5-dihydroxyterephthalic acid to the mixture is 3.5 g / 100 mL; Step 1.3, to a 15% diatomaceous earth suspension, 10% sodium silicate was added, the temperature was raised to 62°C within 2 hours, the pH of the system was adjusted to 6.8, and the reaction was stirred for 35 minutes; 1.2% organic ligand and 6% zinc nitrate were mixed in N,N-dimethylformamide, added to the above diatomaceous earth suspension, stirred and heated to 68°C, and reacted for 24 hours; the pH of the system was adjusted to 7.1, and the reaction was continued for 30 minutes; centrifuged, dried to constant weight at 100°C, and crushed to obtain modified diatomaceous earth; the ratio of organic ligand to N,N-dimethylformamide was 1.3 g / 100 mL; Step 2: Mix the alkoxy-terminated polydimethylsiloxane, the crosslinking agent, the mildew inhibitor, the catalyst, and the fumed silica, and stir and disperse them in a double planetary mixer at a stirring rate of 100 rpm and a dispersion rate of 8000 rpm for 1.5 hours; add the filler and the plasticizer, and continue stirring and dispersing them at a stirring rate of 180 rpm and a dispersion rate of 12000 rpm for 1.5 hours to obtain an alcohol-permeable glue; comprising the following components: 90 parts of alkoxy-terminated polydimethylsiloxane, 10 parts of plasticizer, 12 parts of filler, 2.0 parts of fumed silica, 10 parts of crosslinking agent, 1.8 parts of mildew inhibitor, and 1.2 parts of catalyst; The crosslinking agent includes 32 parts of vinyltrimethoxysilane, 12 parts of diisopropyl bis(ethyl acetoacetate) titanate, 55 parts of 3-aminopropyltrimethoxysilane, 7 parts of [3-(morpholinyl)propyl]trimethoxysilane and 8 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; the filler is a mixture of diatomaceous earth and fumed silica with a mass ratio of 10:0.9; the diatomaceous earth contains 15% modified diatomaceous earth.
[0037] Example 3: A process for preparing a mildew-proof beauty alcohol permeable glue, comprising the following steps: Step 1.1. Add metallic magnesium and iodine to anhydrous tetrahydrofuran, and slowly add thiazolylbenzimidazole-6-bromide under a nitrogen atmosphere. After the addition is complete, raise the temperature to 65° C. and react for 150 minutes to obtain thiazolylbenzimidazole magnesium bromide; the mass ratio of thiazolylbenzimidazole-6-bromide, metallic magnesium, and iodine is 10:1.05:0.4; and the ratio of thiazolylbenzimidazole-6-bromide to anhydrous tetrahydrofuran is 28 g / 100 mL; Magnesium metal and iodine were added to anhydrous tetrahydrofuran, and 4,5-dibromoimidazole was slowly added under nitrogen atmosphere. After the addition was complete, the temperature was raised to 65°C and the reaction was carried out for 150 minutes to obtain imidazolyl magnesium bromide. The mass ratio of 4,5-dibromoimidazole, magnesium metal, and iodine was 10:2.50:0.8; the ratio of 4,5-dibromoimidazole to anhydrous tetrahydrofuran was 28g / 100mL. Mix cyanuric chloride and anhydrous tetrahydrofuran, slowly add thiazolylbenzimidazole magnesium bromide over 30 minutes, and stir to react for 3 hours; add imidazolylmagnesium bromide, heat to 65°C, and stir to react for 3 hours; raise the temperature to 90°C, and continue to react for 2.5 hours; add aqueous ammonium chloride solution, extract with dichloromethane, dry with anhydrous sodium sulfate, filter, and rotary evaporate the filtrate and pass through a column to obtain a dibromo compound; the mass ratio of cyanuric chloride, thiazolylbenzimidazole magnesium bromide, and imidazolylmagnesium bromide is 10:17.3:35.7; the ratio of cyanuric chloride to anhydrous tetrahydrofuran is 15g / 100mL; Step 1.2: 2,5-dihydroxyterephthalic acid, a dibromo compound, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide in a volume ratio of 1:2.5, heated to 105°C, stirred, and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand; the mass ratio of 2,5-dihydroxyterephthalic acid, dibromo compound, and potassium carbonate is 10:29.1:30.7; the ratio of 2,5-dihydroxyterephthalic acid to the mixture is 4 g / 100 mL; Step 1.3, to a 15% diatomaceous earth suspension, 15% sodium silicate was added, the temperature was raised to 65°C within 2 hours, the pH of the system was adjusted to 6.9, and the reaction was stirred for 40 minutes; 2.0% organic ligand and 10% zinc nitrate were mixed in N,N-dimethylformamide, added to the above diatomaceous earth suspension, stirred and heated to 75°C, and reacted for 24 hours; the pH of the system was adjusted to 7.2, and the reaction was continued for 40 minutes; centrifuged, dried to constant weight at 110°C, and crushed to obtain modified diatomaceous earth; the ratio of organic ligand to N,N-dimethylformamide was 1.6 g / 100 mL; Step 2: Mix the alkoxy-terminated polydimethylsiloxane, the crosslinking agent, the mildew inhibitor, the catalyst, and the fumed silica, stir and disperse them in a double planetary mixer at a stirring rate of 120 rpm and a dispersion rate of 9500 rpm for 2 hours; add the filler and the plasticizer, stir and disperse them at a stirring rate of 190 rpm and a dispersion rate of 13000 rpm for 1 hour to obtain an alcohol-permeable glue; comprising the following components: 90 parts of alkoxy-terminated polydimethylsiloxane, 10 parts of plasticizer, 18 parts of filler, 3.5 parts of fumed silica, 15 parts of crosslinking agent, 2.0 parts of mildew inhibitor, and 2.5 parts of catalyst; The crosslinking agent includes 25 parts of vinyltrimethoxysilane, 11 parts of diisopropyl bis(ethyl acetoacetate) titanate, 47 parts of 3-aminopropyltrimethoxysilane, 5 parts of [3-(morpholinyl)propyl]trimethoxysilane and 10 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; the filler is a mixture of diatomaceous earth and fumed silica with a mass ratio of 10:1.5; the diatomaceous earth contains 20% modified diatomaceous earth.
[0038] Comparative Example 1: A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Step 1.1, 2,5-dihydroxyterephthalic acid, 4,5-dibromoimidazole, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide in a volume ratio of 1:2.0, heated to 100°C, stirred and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand; the mass ratio of 2,5-dihydroxyterephthalic acid, 4,5-dibromoimidazole, and potassium carbonate is 10:11.4:15.6; the ratio of 2,5-dihydroxyterephthalic acid to the mixture is 3 g / 100 mL; Step 1.2 and step 2 are the same as step 1.3 and step 2 in Example 1. The mass ratio of diatomaceous earth, sodium silicate, zinc nitrate and organic ligand is 100:5:2:0.22 to obtain alcohol-permeable glue.
[0039] Comparative Example 2: A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Step 1.1, 2,5-dihydroxyterephthalic acid, 1,7-dibromoheptane, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide in a volume ratio of 1:2.0, heated to 100°C, stirred and reacted for 24 hours; cooled to room temperature, centrifuged with water, centrifuged with acetone and methanol, and dried; mixed in water and dimethyl sulfoxide, added with alkali, heated, acidified, centrifuged, washed, and dried to obtain an organic ligand; the mass ratio of 2,5-dihydroxyterephthalic acid, 1,7-dibromoheptane, and potassium carbonate is 10:13.0:16.7; the ratio of 2,5-dihydroxyterephthalic acid to the mixture is 3 g / 100 mL; Step 1.2 and step 2 are the same as step 1.3 and step 2 in Example 1. The mass ratio of diatomaceous earth, sodium silicate, zinc nitrate and organic ligand is 100:5:2:0.24 to obtain alcohol-permeable glue.
[0040] Comparative Example 3: A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Step 1: Add 5% sodium silicate to a 15% diatomaceous earth suspension, heat to 60°C within 2 hours, adjust the pH of the system to 6.5, and stir to react for 30 minutes; mix 0.06% 2-methylimidazole and 2% zinc nitrate in N,N-dimethylformamide, add to the above diatomaceous earth suspension, stir and heat to 60°C, and react for 24 hours; adjust the pH of the system to 6.9, and continue to react for 20 minutes; centrifuge, dry to constant weight at 90°C, and crush to obtain modified diatomaceous earth; the ratio of organic ligand to N,N-dimethylformamide is 1.0 g / 100 mL Step 2 is the same as step 1.3 and step 2 in Example 1, to obtain alcohol-permeable glue.
[0041] Comparative Example 4: A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Step 1: Add 5% sodium silicate and 2% zinc nitrate to a 15% diatomaceous earth suspension, heat to 60°C within 2 hours, adjust the pH of the system to 6.7, and stir to react for 60 minutes; centrifuge, dry to constant weight at 90°C, and grind to obtain modified diatomaceous earth; the ratio of organic ligand and N,N-dimethylformamide is 1.0 g / 100 mL; Step 2 is the same as in Example 1 to obtain alcohol-permeable glue.
[0042] Comparative Example 5: A preparation process of a mildew-proof beauty alcohol permeable glue, comprising the following processes: Step 1: diatomaceous earth and anhydrous ethanol are mixed, stirred and heated to 55°C, 8% surfactant sodium lauryl sulfate is added, and stirred for 12 hours; centrifuged, dried to constant weight, ground, and sieved to obtain modified diatomaceous earth; the ratio of diatomaceous earth to anhydrous ethanol is 20g / 100mL; Step 2: The crosslinking agent is 40 parts of vinyltrimethoxysilane, 13 parts of diisopropyl bis(ethyl acetoacetate) titanate, and 62 parts of 3-aminopropyltrimethoxysilane; the plasticizer includes dimethyl silicone oil; the other processes are the same as those in Example 1 to obtain alcohol-permeable glue.
[0043] Experiment: The alcohol-permeable glue obtained in Examples 1-3 and Comparative Examples 1-5 was cured at 23°C and 50% RH for 3 days and at 50°C for 4 days to prepare samples. The properties of the samples were tested and the test results were recorded: Mechanical properties test: GB / T 14683 is used as the reference standard, and a universal tensile testing machine is used to test the tensile strength of the sample; Surface drying time test: Under the experimental conditions of 23±2℃ and 50±5%RH, touch the surface of the alcohol-permeable glue with your hand every one minute, and record the time it takes for the surface of the alcohol-permeable glue to form a skin as the surface drying time; Anti-mildew performance test: GB / T 1741 is used as the reference standard to test the anti-mildew level of the sample; Hydrothermal stability test: Soak the sample in 50℃ tap water for 10 days, take it out and wash it with water, wipe it dry with filter paper, and dry it at 50℃ for 3 minutes; after the experiment, test the mildew resistance level of the sample again.
[0044] According to the data in the above table, we can clearly draw the following conclusions: The alcohol-permeable adhesive obtained in Example 1-3 was compared with the alcohol-permeable adhesive obtained in Comparative Example 1-5. The test results show that: Compared to the comparative examples, the alcohol-permeable adhesives obtained in Examples 1-3 exhibited higher tensile strength data and shorter open-air times, and exhibited good mildew resistance ratings both before and after hydrothermal treatment. This demonstrates that the present invention improves the mechanical properties, mildew resistance, and hydrothermal stability of the alcohol-permeable adhesives.
[0045] Compared to Example 1, the organic ligand in Comparative Example 1 was prepared from 2,5-dihydroxyterephthalic acid and 4,5-dibromoimidazole; the organic ligand in Comparative Example 2 was prepared from 2,5-dihydroxyterephthalic acid and 1,7-dibromoheptane; the organic ligand in Comparative Example 3 was replaced with 2-methylimidazole; no organic ligand was provided in Comparative Example 4; and the diatomaceous earth was modified with sodium lauryl sulfate in Comparative Example 5. The alcohol-permeable adhesives obtained in Comparative Examples 1-5 showed deterioration in tensile strength and open-air time, and their mildew resistance rating dropped significantly after hydrothermal treatment. This indicates that the present invention's design of the alcohol-permeable adhesive components and process can promote comprehensive improvements in mechanical properties, mildew resistance, and hydrothermal stability, helping to maintain long-lasting and stable mildew resistance.
[0046] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.
Claims
1. A mildew-proof beauty alcohol permeable glue, characterized by: The invention comprises the following components: 80 to 100 parts of alkoxy-terminated polydimethylsiloxane, 7 to 20 parts of plasticizer, 6 to 18 parts of filler, 0.6 to 3.5 parts of fumed silica, 5 to 15 parts of crosslinking agent, 1.2 to 2.0 parts of mildewproofing agent and 0.2 to 2.5 parts of catalyst.
2. The mildew-proof beauty alcohol permeable glue according to claim 1, characterized in that: The crosslinking agent is a mixture of one or more of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, [3-(morpholinyl)propyl]trimethoxysilane, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and diisopropyl bis(ethyl acetoacetate)titanate.
3. The mildew-proof beauty alcohol permeable glue according to claim 1, characterized in that: The plasticizer is a mixture of one or more of methyl silicone oil, dimethyl silicone oil, white oil, diisononyl phthalate, and quaternary ammonium modified silicone oil.
4. A process for preparing a mildew-proof beauty alcohol permeable glue, characterized in that: Including the following processes: Alkoxy-terminated polydimethylsiloxane, a cross-linking agent, a mildew inhibitor, a catalyst, and fumed silica are mixed, and the mixture is stirred and dispersed in a double planetary mixer for 1 to 2 hours; fillers and plasticizers are added, and the mixture is stirred and dispersed for another 1 to 2 hours to obtain an alcohol-permeable adhesive.
5. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 4, characterized in that: The filler is a mixture of diatomaceous earth and fumed silica, with a mass ratio of 10:(0.3-1.5).
6. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 5, characterized in that: The diatomaceous earth is modified, and the specific modification process is as follows: Add silicate to the diatomaceous earth suspension, raise the temperature to 60-65°C within 2 hours, adjust the pH of the system to 6.5-7.0, and stir the reaction for 30-40 minutes; The organic ligand and zinc nitrate are mixed in N,N-dimethylformamide, added to the above diatomaceous earth suspension, stirred and heated to 60-75°C, and reacted for 24-72 hours; the pH of the system is adjusted to 6.9-7.3, and the reaction is continued for 20-40 minutes to obtain modified diatomaceous earth.
7. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 6, characterized in that: The organic ligand is prepared by the following process: 2,5-dihydroxyterephthalic acid, a dibromo compound, and potassium carbonate are mixed in a mixture of acetone and dimethyl sulfoxide, heated to 100-105° C., and stirred for reaction for 24 hours to obtain an organic ligand.
8. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 7, characterized in that: The dibromo compound is prepared by the following process: Mix cyanuric chloride and anhydrous tetrahydrofuran, slowly add thiazolylbenzimidazole magnesium bromide, add completely over 30 minutes, and stir to react for 2 to 3 hours; add imidazolylmagnesium bromide, heat to 60 to 65°C, and stir to react for 2 to 3 hours; raise the temperature to 85 to 90°C, and continue to react for 2.5 to 3.5 hours to obtain a dibromo compound.
9. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 6, characterized in that: The mass ratio of diatomaceous earth, silicate, zinc nitrate and organic ligand is 100: (5-15): (2-10): (0.4-2.0).
10. The process for preparing the mildew-proof cosmetic alcohol adhesive according to claim 8, characterized in that: The mass ratio of cyanuric chloride, thiazolylbenzimidazole magnesium bromide and imidazolylmagnesium bromide is 10:(16.5-17.3):(32.7-35.7).
Citation Information
Cited By
Preparation method of dealcoholized environment-friendly mildew-proof beautifying gel for home decoration
CN121022342A